PERANCANGAN UI MOBILE LEARNING DENGAN MATERI ILUSTRASI BAGI SISWA SEKOLAH MENENGAH KEJURUAN (SMK) - Murni, Endri Sintiana; Alimin, Nurhayatu Nufut; Yunianti, Esterica; Joko, Joko (Universitas Negeri Makassar, 2025)
Learning in Vocational Schools is a pioneer for the industry to develop. DKV students with the development of the times also need to know the development of technology. So, knowledge of illustrations in digital form is important in learning. The problem at SMK N 9 Surakarta majoring in DKV based on a questionnaire of 55.8% shows that illustration material is difficult to understand. This study aims to develop teaching materials in the form of interactive android-based media for vocational school students is expected to help students learn it easily and can be accessed anywhere. The research method uses research and development research with the stages of problem identification, analysis, design, and development. The results of the study are in the form of a mobile learning UI design with teaching material content packaged in an application with visualization of color elements, typography, and illustrations. The Wireframe design of the illustration material application is made with a storyboard containing the initial display, material competencies, works, questions, and references. The visual elements in the application use blue, Tw Cen MT and Futura fonts. The illustrations used are cartoons, caricatures, and comics. The prototype splash screen is blue and consists of various types of illustration materials. The benefits generated from the application are that students learn it with an easily UI display.